Extreme-QTL mapping of monepantel resistance in Haemonchus contortus - Niciura, Simone Cristina Méo; Tizioto, Polyana Cristine; Moraes, Caroline Valério; Cruvinel, Giovanna Gabrielle; De Albuquerque, Ana Cláudia Alexandre [UNESP]; Santana, Raul Costa Mascarenhas; Chagas, Ana Carolina De Souza; Esteves, Sergio Novita; Benavides, Magda Vieira; Do Amarante, Alessandro Francisco Talamini [UNESP] (Springer Nature, 2019)
Background: Haemonchus contortus, a gastrointestinal nematode parasite of sheep, is mainly controlled by anthelmintics; the occurrence of anthelmintic resistance leads to treatment failures and increases economic burden. Because molecular mechanisms involved in drug resistance can be elucidated by genomic studies, an extreme quantitative trait locus (X-QTL) mapping approach was used to identify co-segregation of the resistance phenotype with genetic markers to detect the genome-wide variants associated with monepantel resistance in H. contortus. Methods: A cross between H. contortus isolates using parental susceptible (Par-S) males and monepantel resistant (Par-R) females resulted in SR progeny, while reciprocal cross resulted in RS progeny. Pools (n = 30,000) of infective larvae (L3) recovered from Par-R, and from SR and RS populations in the F3 generation, collected both before (unselected group) and 7 days after (selected group) selection with monepantel treatment in sheep hosts, were subjected to genome sequencing (Pool-Seq). Pairwise comparisons of allele frequencies between unselected and selected groups were performed for each population by Fisher's exact test (FET) and for both populations combined by a Cochran-Mantel-Haenszel (CMH) test. Results: Mapping rates varied from 80.29 to 81.77% at a 90.4X mean coverage of aligned reads. After correction for multiple testing, significant (P < 0.05) changes in allele frequencies were detected by FET for 6 and 57 single nucleotide polymorphisms (SNPs) in the SR and RS populations, respectively, and by the CMH test for 124 SNPs in both populations. The significant variants located on chromosome 2 generated a selection signal in a genomic region harboring the mptl-1, deg-3 and des-2 genes, previously reported as candidates for monepantel resistance. In addition, three new variants were identified in the mptl-1 gene. Conclusions: This study expands knowledge on genome-wide molecular events underlying H. contortus resistance to monepantel. The identification of a genome region harboring major genes previously associated with monepantel resistance supports the results of the employed X-QTL approach. In addition, a deletion in exon 11 of the mptl-1 gene should be further investigated as the putative causal mutation leading to monepantel resistance.
Keywords: Anthelmintic resistance; Drug resistance; F2 mapping; Genome sequencing; Sheep gastrointestinal nematodes